CHARACTER EDUCATION TO RESPOND TO THE 21st CENTURY SKILLS CHALLENGES: A REVIEW - Wawan, Indra Darmawan (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2021)
As has been studied by experts, it has created challenges that have an impact on the occurrence of a crisis in the field of character. The purpose of writing this article is to answer the challenges of 21st century skills through character education. Daniel Bell as quoted by Mochtar Buchori mentions there are six challenges in the 21st century; namely integration of economy, fragmentation of politics, interdependence, high technology, and new colonization in culture. Character education as mentioned above, among others, is aimed at the emergence of attitudes and concerns to command the good and stay away from the bad. The method used in this research is literatur review. Character education in order to answer the challenges of the 21st century in the nation is something that needs to be done. Through such character education, it will be possible to produce cadres of national leaders who have a strong commitment to advancing the nation and state, have a clear identity, and are not carried away by globalization